Effect of multiple hook heights and positions during en masse maxillary distalization using infrazygomatic crest miniscrew– single and double points of force application: a finite element analysis study - Maxim Fares; Wessam Marzouk; Hanan A. Ismail; Yasser Abuouf; Hassan E. Kassem (BMC Oral Health)
Abstract Background This study aimed to simulate maxillary dentition distalization as one unit anchored to infrazygomatic crest (IZC) miniscrew using different hook positions and lengths. Materials and methods Eleven finite-element models (FEM) were constructed from a cone beam computed tomography scan of a patient with Class II malocclusion. Different force vectors to the IZC miniscrew were simulated using one point of force application either mesial to the canine or mesial to the first premolar, using different hook lengths (0, 2, 4, and 6 mm). In the novel approach, two point-force system was constructed using double-hook retraction in three conditions. The FEM yielded tooth displacement patterns and stress contour plots of the periodontal ligament. Results When hooks were placed mesial to the canine, the incisor showed palatal translation with controlled palatal tipping at 0 and 2 mm, palatal bodily displacement at 4 mm, and palatal translation with torquing at 6 mm. In hooks mesial to the first premolar, the pattern showed palatal translation with torquing, except with the 0-mm hook where controlled palatal tipping occurred. Whereas, vertically, it shows extrusion at the 0- and 2-mm hooks mesial to the first premolar and intrusion with the remaining single hook simulations. The molar exhibited translation with controlled distal tipping at all hook lengths mesial to the canine and 0 mm mesial to the first premolar, while it demonstrated distal translation with torquing at 2-,4-, and 6-mm hooks mesial to the first premolar. Vertically, it showed extrusion with hooks mesial to the canine, which changed to intrusion with hooks mesial to the first premolar. In double-hook simulations, the incisor showed bodily displacement only with hooks mesial to the canine and second premolar, whereas the molar showed distal bodily movement with hooks mesial to the first and second premolars. Conclusion Hook height and position variations are crucial in the resultant displacement pattern. Accordingly, different force systems should be tailored individually based on the patient’s initial malocclusion.